Conductive performance detection method and system for battery
By collecting and analyzing the battery manufacturing process parameters and conductivity detection parameters and evaluating the conductivity index, the problem of insufficient accuracy in the evaluation of the overall conductivity of the material in the prior art is solved, and a comprehensive and accurate evaluation and optimization of the battery's conductivity is achieved.
Patent Information
- Application Number
- CN202411658552.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing material conductivity detection technology has limitations, mainly concentrated on the surface of the material, which leads to difficulty in accurately judging the overall conductivity of the material, which in turn affects the accurate evaluation of the material.
By collecting battery manufacturing process parameters, analyzing the manufacturing process deterioration factors, combining conductivity detection parameters, evaluating the conductivity index, matching expected and actual conductivity levels, and then adjusting the manufacturing process parameters to improve the conductivity.
It realizes a comprehensive and accurate evaluation of the battery's conductivity, reduces errors in one-sided analysis, and can promptly detect conductive performance problems and optimize them to ensure that the conductivity is at a high level.
Smart Images

Figure CN119535212A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery performance detection, and in particular to a method and system for detecting the conductivity of a battery. Background Art
[0002] With the rapid development of materials science and electronic technology, conductivity is a key indicator for measuring the electrical properties of materials. Its accurate detection is crucial to the fields of material research and development, electronic device design and manufacturing. Therefore, researchers are constantly exploring new detection technologies to achieve more accurate and faster conductivity detection to promote the continuous progress of materials science and electronic information technology.
[0003] For example, the invention patent with announcement number CN116165458B announces a device and method for detecting the conductive properties of graphene conductive slurry, including a detection table, a detection barrel, a slurry storage tube, an electrode sheet, a No. 1 electrode ring, a top cover, an electrode rod, a No. 2 electrode ring and a heating coil; the prepared graphene conductive slurry is evenly filled into the interior of the slurry storage tube, and the slurry storage tube is evenly placed in the interior of the detection barrel so that the electrode sheet at the bottom of the slurry storage tube is connected to the No. 1 electrode ring, and the top cover is installed on the top of the detection barrel so that the lower end of the electrode rod contacts the top of the graphene conductive slurry inside the slurry storage tube, and the heating temperature of the heating coil is controlled through the operation panel of the detection table to adjust the temperature of the graphene conductive slurry to simulate the temperature changes of the battery during charging and discharging in actual use, and at the same time, the changes in voltage, current and resistance are controlled through the operation panel of the detection table to detect the conductive properties of the graphene conductive slurry.
[0004] For example, the invention patent with publication number CN116203421A discloses a battery detection device and a battery detection method. The battery detection device includes a supporting mechanism, a first conductive component and a second conductive component. The supporting mechanism is used to place a plurality of battery cells arranged in sequence, and each battery cell includes a first electrode terminal and a second electrode terminal with opposite polarities; the first conductive component includes a plurality of detection parts and a plurality of conductive parts, and the plurality of detection parts are respectively electrically connected to the first electrode terminals of the plurality of battery cells, and the conductive part connects two adjacent detection parts, and a current detection component is arranged on each conductive part; the second conductive component is used to be electrically connected to the second electrode terminal pieces of the plurality of battery cells.
[0005] However, in the process of implementing the embodiments of the present application, it was found that the above-mentioned technology has at least the following technical problems: the existing material conductivity detection technology has a significant limitation, that is, the evaluation is mainly concentrated on the surface of the material, and the analysis of the material's conductivity is relatively one-sided. This limitation ultimately affects the accurate judgment of the overall conductivity of the material, resulting in the evaluation of the material's conductivity being not accurate and comprehensive enough. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a method and system for detecting the conductivity of a battery, which can effectively solve the problems involved in the above-mentioned background technology.
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions: The first aspect of the present invention provides a method for detecting the conductivity of a battery, including: S1. Collecting battery manufacturing process parameters, analyzing the manufacturing process degradation factor of the battery, and matching the expected conductivity level of the battery; S2. Obtaining the conductivity detection parameters of the battery, and combining the manufacturing process degradation factor of the battery, evaluating the conductivity performance index of the battery, and matching the actual conductivity level of the battery; S3. Comparing the expected conductivity level of the battery with the actual conductivity level of the battery. If the expected conductivity level of the battery is less than or equal to the actual conductivity level of the battery, continue manufacturing using the battery manufacturing process parameters. Otherwise, adjust the battery manufacturing process parameters; S4. Based on the expected conductivity level of the battery, the actual conductivity level of the battery and the conductivity performance index of the battery, determine the adjustment requirement index of the battery, and adjust the battery manufacturing process parameters accordingly.
[0008] As a further method, the expected conductivity level of the battery is matched, and the specific matching process is: matching the manufacturing process degradation factor of the battery with the expected conductivity level corresponding to each manufacturing process degradation factor interval stored in the detection database, thereby obtaining the expected conductivity level of the battery.
[0009] As a further method, the actual conductivity level of the battery is matched, and the specific matching process is: matching the conductivity performance index of the battery with the actual conductivity level corresponding to each conductivity performance index interval stored in the detection database, thereby obtaining the actual conductivity level of the battery.
[0010] As a further method, the battery manufacturing process parameters are adjusted, and the specific analysis process is: matching the battery's adjustment requirement index with the manufacturing adjustment set corresponding to each adjustment requirement index interval stored in the detection database, thereby obtaining the battery's manufacturing adjustment set, and adjusting the battery manufacturing process parameters according to the battery's manufacturing adjustment set.
[0011] The second aspect of the present invention provides a system for applying the method for detecting the conductivity of a battery as described above, comprising: an expected conductivity analysis module, used to collect battery manufacturing process parameters, analyze the manufacturing process degradation factor of the battery, and match the expected conductivity level of the battery; an actual conductivity evaluation module, used to obtain the conductivity detection parameters of the battery, and evaluate the conductivity performance index of the battery in combination with the manufacturing process degradation factor of the battery, and match the actual conductivity level of the battery; a conductivity level comparison module, used to compare the expected conductivity level of the battery with the actual conductivity level of the battery, if the expected conductivity level of the battery is less than or equal to the actual conductivity level of the battery, then the battery manufacturing process parameters are used to continue manufacturing, otherwise, the battery manufacturing process parameters are adjusted; a battery manufacturing adjustment module, used to determine the adjustment requirement index of the battery based on the expected conductivity level of the battery, the actual conductivity level of the battery and the conductivity performance index of the battery, thereby adjusting the battery manufacturing process parameters.
[0012] Compared with the prior art, the embodiments of the present invention have at least the following advantages or beneficial effects:
[0013] (1) The present invention provides a method and system for detecting the conductivity of a battery. By collecting and analyzing the parameters of the manufacturing process of a glass-ceramic sulfide battery, the expected conductivity level of the glass-ceramic sulfide battery is scientifically and accurately matched, and the conductivity detection parameters of the glass-ceramic sulfide battery are obtained and evaluated, so as to scientifically and accurately match the actual conductivity level of the glass-ceramic sulfide battery. Through comprehensive and in-depth data collection and analysis, the conductivity of the glass-ceramic sulfide battery can be quickly and accurately judged, reducing the error and uncertainty caused by one-sided analysis. If the expected conductivity level of the glass-ceramic sulfide battery is less than or equal to the actual conductivity level of the glass-ceramic sulfide battery, the glass-ceramic sulfide battery manufacturing process parameters are used to continue manufacturing. Otherwise, timely feedback can be provided to guide the adjustment of the parameters of the glass-ceramic sulfide battery manufacturing process, thereby ensuring that the conductivity of the glass-ceramic sulfide battery is at a high level.
[0014] (2) The present invention derives the conductivity level of the glass-ceramic sulfide battery from two aspects, namely the manufacturing process of the glass-ceramic sulfide battery and the conductivity detection of the glass-ceramic sulfide battery, and performs comparative analysis, thereby being able to analyze the conductivity performance of the glass-ceramic sulfide battery from multiple dimensions, reducing the one-sidedness of single-dimensional analysis, and timely discovering the conductivity performance problems of the glass-ceramic sulfide battery, thereby providing a data basis for optimizing the conductivity performance of the glass-ceramic sulfide battery.
[0015] (3) By analyzing the expected conductivity level of the glass-ceramic sulfide battery, the actual conductivity level of the glass-ceramic sulfide battery and the conductivity performance index of the glass-ceramic sulfide battery, the present invention can accurately evaluate the current status and potential improvement space of the conductivity performance of the glass-ceramic sulfide battery, and then scientifically determine the degree of adjustment required for the glass-ceramic sulfide battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The present invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the present invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.
[0017] Figure 1 The figure is a schematic flow chart of the method steps of the present invention.
[0018] Figure 2 It is a schematic diagram of system module connection of the present invention.
[0019] Figure 3 It is a schematic diagram of the conductivity change curve involved in the present invention.
[0020] Figure numerals: 1. Sample testing point. DETAILED DESCRIPTION
[0021] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0022] It should be explained that this embodiment is specifically analyzed based on microcrystalline glassy sulfide batteries.
[0023] Reference Figure 1 As shown, the first aspect of the present invention provides a method for detecting the conductivity of a battery, comprising: S1. collecting parameters of a microcrystalline glassy sulfide battery manufacturing process, analyzing degradation factors of the microcrystalline glassy sulfide battery manufacturing process, and matching the expected conductivity level of the microcrystalline glassy sulfide battery.
[0024] The above-mentioned microcrystalline glass sulfide battery manufacturing process parameters include average sintering temperature, sintering time, average molding pressure and component ratio. In addition to being applicable to the above-mentioned parameters, this example can also be used for other parameters; the above-mentioned microcrystalline glass sulfide battery manufacturing process includes raw material preparation stage, electrode preparation stage, electrode preparation stage, battery assembly stage and sintering stage.
[0025] Specifically, the expected conductivity level of the glass-ceramic sulfide battery is matched, and the specific matching process is: matching the manufacturing process degradation factor of the glass-ceramic sulfide battery with the expected conductivity level corresponding to each manufacturing process degradation factor interval stored in the detection database, thereby obtaining the expected conductivity level of the glass-ceramic sulfide battery; wherein the manufacturing process degradation factor of the glass-ceramic sulfide battery is negatively correlated with the expected conductivity level. For example, if the manufacturing process degradation factor of the glass-ceramic sulfide battery is T, it belongs to the expected conductivity level stored in the detection database. The manufacturing process degradation factor interval is [T-17%, T+43%], and the expected conductivity level corresponding to the manufacturing process degradation factor interval [T-17%, T+43%] is D. Then the expected conductivity level of the microcrystalline glassy sulfide battery is D. If the manufacturing process degradation factor of the microcrystalline glassy sulfide battery is T+50%, it belongs to the manufacturing process degradation factor interval [T+43%, T+103%] stored in the detection database. The expected conductivity level corresponding to the manufacturing process degradation factor interval [T+43%, T+103%] is D-1.
[0026] It should also be explained that the manufacturing process parameters of glassy sulfide microcrystalline batteries are formulated by battery R&D engineers based on parameters such as the average sintering reference temperature stored in the detection database. Therefore, it is expected that the expected conductivity level of the glassy sulfide microcrystalline batteries is at a high level. However, the average sintering reference temperature stored in the detection database is based on a large number of battery manufacturing practices and can reflect the general rules in the manufacturing process of most glassy sulfide microcrystalline batteries. However, in the actual manufacturing process, due to the complexity and uncertainty of various factors such as the production environment, equipment and manufacturing materials, the manufacturing process is affected differently, resulting in the actual conductivity level of the glassy sulfide microcrystalline battery being lower than the expected conductivity level of the glassy sulfide microcrystalline battery. Therefore, it is also necessary to determine the adjustment demand index of the glassy sulfide microcrystalline battery to clarify the specific degree of adjustment, so as to retrieve targeted adjustment plans from the detection database to adjust the manufacturing process parameters of the glassy sulfide microcrystalline battery.
[0027] Specifically, the manufacturing process degradation factor of the glass-ceramic sulfide battery is analyzed, and the specific analysis process is: extracting the average sintering temperature of the glass-ceramic sulfide battery in the manufacturing monitoring cycle, the sintering time of the glass-ceramic sulfide battery in the manufacturing monitoring cycle, and the average molding pressure of the glass-ceramic sulfide battery in the manufacturing monitoring cycle from the glass-ceramic sulfide battery manufacturing process parameters; the above-mentioned manufacturing monitoring cycle refers to the time period for monitoring the production and manufacturing process of the glass-ceramic sulfide battery, and the specific duration is determined by the battery R&D engineer according to the production and manufacturing requirements of the glass-ceramic sulfide battery; the average sintering temperature of the glass-ceramic sulfide battery in the manufacturing monitoring cycle, the sintering time of the glass-ceramic sulfide battery in the manufacturing monitoring cycle, and the average molding pressure of the glass-ceramic sulfide battery in the manufacturing monitoring cycle can all be extracted from the intelligent control system.
[0028] It should be explained that the above-mentioned intelligent control system can monitor and control the key parameters of the manufacturing process in real time during the manufacturing process of microcrystalline glass sulfide batteries, and collect key data of the manufacturing process in real time through various sensors (such as temperature sensors, pressure sensors and time sensors, etc.) installed on the microcrystalline glass sulfide battery production line. These sensors can accurately measure parameters such as sintering temperature, sintering time and molding pressure, and transmit the data to the intelligent control system. The intelligent control system will perform real-time analysis and processing on the collected data (such as mean processing, variance processing, extreme value processing and integral processing, etc.). The intelligent control system will also automatically adjust the manufacturing parameters in the manufacturing process to ensure that each step of the microcrystalline glass sulfide battery manufacturing process is carried out according to the preset parameters, thereby improving the accuracy and quality of the microcrystalline glass sulfide battery.
[0029] The composition ratio of each key material of the microcrystalline glass sulfide battery at the starting time of the manufacturing monitoring cycle is extracted from the manufacturing process parameters of the microcrystalline glass sulfide battery, thereby comprehensively obtaining an analysis method for the manufacturing process degradation factor of the microcrystalline glass sulfide battery; the composition ratio of each key material of the above-mentioned microcrystalline glass sulfide battery at the starting time of the manufacturing monitoring cycle is formulated by battery R&D engineers based on chemical reaction principles, chemical properties, thermal stability and electrical conductivity of key materials; wherein the key materials include but are not limited to lauroyl ammonium salt, lithium borohydride, lithium sulfide, phosphorus pentasulfide, nickel sulfide, cobalt sulfide, lithium silicon alloy and lithium tin alloy.
[0030] Further, the manufacturing process degradation factor of the glass-ceramic sulfide battery, in this embodiment, is obtained by comprehensive analysis of the average sintering temperature, sintering time, average molding pressure of the glass-ceramic sulfide battery during the manufacturing monitoring cycle and the composition ratio of each key material of the glass-ceramic sulfide battery at the starting time of the manufacturing monitoring cycle, and is used to represent the numerical value of the degree of degradation of the conductive performance of the glass-ceramic sulfide battery caused by the manufacturing process of the glass-ceramic sulfide battery. The specific analysis method is:
[0031]
[0032] ST is the average sintering temperature of the glass-ceramic sulfide battery during the manufacturing monitoring cycle, which refers to the average temperature experienced by the glass-ceramic sulfide battery during the sintering stage.
[0033] SD is the sintering time of the glassy sulfide microcrystalline battery during the manufacturing monitoring cycle, which refers to the time the glassy sulfide microcrystalline battery spends in the sintering stage. Too short a sintering time may result in the failure of key materials to fully react or densify, while too long a sintering time may result in excessive crystallization or decomposition of key materials.
[0034] PD is the average molding pressure of the glass-ceramic sulfide battery during the manufacturing monitoring cycle, which refers to the average pressure applied when the glass-ceramic sulfide battery is molded during the manufacturing process of the glass-ceramic sulfide battery.
[0035] CR s It is the composition ratio of the sth key material of the microcrystalline glassy sulfide battery at the starting time of the manufacturing monitoring cycle, which refers to the composition ratio of each key material determined at the beginning of the manufacturing monitoring cycle during the manufacturing process of the microcrystalline glassy sulfide battery.
[0036] ΔST is the average sintering reference temperature preset in the detection database, which represents the reference value of the average sintering temperature of the microcrystalline glassy sulfide battery during the manufacturing monitoring cycle.
[0037] ΔSD is the sintering reference time preset in the detection database, which represents the reference value of the sintering time of the microcrystalline glassy sulfide battery during the manufacturing monitoring cycle.
[0038] ΔPD is the average molding reference pressure preset in the detection database, which represents the reference value of the average molding pressure of the microcrystalline glassy sulfide battery during the manufacturing monitoring cycle.
[0039] ΔCR sTo detect the reference composition ratio of the sth key material preset in the database, it represents the reference value of the composition ratio of the sth key material of the microcrystalline glassy sulfide battery at the starting time of the manufacturing monitoring cycle.
[0040] e is a natural constant, s is the serial number of each key material, s = {1, 2, 3, ..., p}, and p is the total number of key materials.
[0041] Among them, MPD is the degradation factor of the manufacturing process of microcrystalline glass sulfide batteries. In the manufacturing process of microcrystalline glass sulfide batteries, when the proportion of each key component deviates significantly from the corresponding reference component proportion, it will directly lead to a decrease in the density of the microcrystalline glass structure. This change will in turn weaken the ionic conductivity and mechanical strength of the battery. At the same time, if the average sintering temperature deviates significantly from the average sintering reference temperature, it will aggravate the imperfection of the microcrystalline structure and further reduce the performance of the battery. It should be noted that there is a close dependence between the sintering time and the average sintering reference temperature. They jointly determine the completion of the sintering process and the final quality of the sintered body. Specifically, if the sintering time deviates significantly from the sintering reference time, it will not only directly affect the sintering temperature, but also lead to insufficient material migration and crystal phase transformation during the sintering process. Thereby reducing the stability of the microcrystalline structure inside the glass-ceramic sulfide battery, this insufficient stability will further affect the electrochemical and mechanical properties of the glass-ceramic sulfide battery, causing the performance of the glass-ceramic sulfide battery to decline during long-term use. If the pressure applied during molding deviates significantly from the average molding reference pressure at this time, then under the condition of unstable microcrystalline structure inside the glass-ceramic sulfide battery, the conductivity and other physical properties of the glass-ceramic sulfide battery may be further affected. These unfavorable factors are superimposed on each other, indicating that the glass-ceramic sulfide battery is more likely to have quality problems in the manufacturing process, which in turn has a significant negative impact on the overall performance of the glass-ceramic sulfide battery, resulting in reduced conductivity, reliability and durability of the glass-ceramic sulfide battery.
[0042] S2. Obtain the conductivity detection parameters of the glass-ceramic sulfide battery, and combine the degradation factor of the manufacturing process of the glass-ceramic sulfide battery to evaluate the conductivity performance index of the glass-ceramic sulfide battery and match the actual conductivity level of the glass-ceramic sulfide battery.
[0043] The above-mentioned conductivity detection parameters include free electron concentration, actual density, porosity, conductivity change curve and average discharge power. In addition to being applicable to the above-mentioned parameters, this example can also be applied to other parameters.
[0044] In a specific embodiment, the present invention derives the conductivity level of the glass-ceramic sulfide battery from two aspects, namely the manufacturing process of the glass-ceramic sulfide battery and the conductivity detection of the glass-ceramic sulfide battery, and performs comparative analysis, thereby being able to analyze the conductivity of the glass-ceramic sulfide battery from multiple dimensions, reducing the one-sidedness of single-dimensional analysis, and timely discovering the conductivity problems of the glass-ceramic sulfide battery, thereby providing a data basis for optimizing the conductivity of the glass-ceramic sulfide battery.
[0045] Specifically, the obtaining of the conductivity detection parameters of the glass-ceramic sulfide battery refers to conducting a conductivity detection test on the glass-ceramic sulfide battery and obtaining the conductivity detection parameters of the glass-ceramic sulfide battery during the test cycle; the above-mentioned test cycle refers to the time period for the conductivity detection test of the glass-ceramic sulfide battery, and the specific duration will vary according to the actual situation during the actual test process; the above-mentioned conductivity detection test on the glass-ceramic sulfide battery, the specific test process is: controlling different temperature conditions to simulate various temperature conditions that the glass-ceramic sulfide battery may encounter in the actual use environment, usually selecting a series of representative temperature points, such as room temperature, high temperature (close to or slightly higher than the upper limit of the battery's operating temperature) and low temperature (close to or slightly lower than the battery's minimum operating temperature), etc., to measure the conductivity performance, at each temperature point, after maintaining stability for a period of time, using a high-precision ammeter and voltmeter, respectively measure the current and voltage responses of the glass-ceramic sulfide battery, thereby calculating the battery's conductivity performance parameters, such as conductivity, etc.
[0046] Specifically, the actual conductivity level of the glass-ceramic sulfide battery is matched, and the specific matching process is: matching the conductivity performance index of the glass-ceramic sulfide battery with the actual conductivity level corresponding to each conductivity performance index interval stored in the detection database, thereby obtaining the actual conductivity level of the glass-ceramic sulfide battery, wherein the conductivity performance index of the glass-ceramic sulfide battery is positively correlated with the actual conductivity level. In an exemplary embodiment, assuming that the conductivity performance index of the glass-ceramic sulfide battery is B, which belongs to the conductivity performance index interval stored in the detection database The actual conductivity grade corresponding to the conductivity performance index interval [B-35%, B+35%] is G, so the actual conductivity grade of the microcrystalline glassy sulfide battery is G. Assuming that the conductivity performance index of the microcrystalline glassy sulfide battery is B+50%, it belongs to the conductivity performance index interval [B+35%, B+105%] stored in the detection database, and the actual conductivity grade corresponding to the conductivity performance index interval [B+35%, B+105%] is G+1, then the actual conductivity grade of the microcrystalline glassy sulfide battery is G+1.
[0047] Furthermore, the conductivity index of the glass-ceramic sulfide battery is evaluated, and the specific evaluation process is as follows:
[0048] The free electron concentration of the glass-ceramic sulfide battery at the end of the test cycle, the actual density of the glass-ceramic sulfide battery at the end of the test cycle, and the porosity of the glass-ceramic sulfide battery at the end of the test cycle are extracted from the conductive detection parameters of the glass-ceramic sulfide battery during the test cycle; the free electron concentration of the glass-ceramic sulfide battery at the end of the test cycle is obtained by an electrochemical test method, such as the Hall effect test. The Hall effect test is a non-contact measurement method that can accurately determine the material's carrier type, concentration, mobility and other parameters. At the end of the test cycle, the glass-ceramic sulfide battery is The glassy sulfide battery is placed in a Hall effect tester. A magnetic field and current are applied. The direction of the magnetic field should be perpendicular to the direction of the applied current. A known current is applied through the microcrystalline glassy sulfide battery. This current will cause the free electrons inside the microcrystalline glassy sulfide battery to deflect under the action of the magnetic field. A highly sensitive voltmeter is used to measure the voltage difference generated on both sides of the microcrystalline glassy sulfide battery sample (i.e., perpendicular to the direction of the magnetic field and the current). This voltage difference is called the Hall voltage. The magnitude of the Hall voltage is related to the magnetic field strength, the current magnitude, and the material properties of the battery sample. The Hall coefficient is calculated from this. The Hall coefficient is a material Intrinsic properties, which can be calculated by the ratio of Hall voltage, current and magnetic field strength. Specifically, the Hall coefficient is equal to the Hall voltage divided by the product of current and magnetic field strength, divided by the thickness of the microcrystalline glassy sulfide battery. Finally, using the known values of the Hall coefficient and the electron charge, the free electron concentration can be calculated. The free electron concentration is equal to the inverse of the electron charge divided by the Hall coefficient. The actual density of the above-mentioned microcrystalline glassy sulfide battery at the end of the test cycle is calculated using the Archimedes drainage method. The Archimedes drainage method is a measurement method based on the buoyancy principle that can accurately determine the density of the material. At the end of the test cycle, First, the mass and volume of the microcrystalline glassy sulfide battery are measured, and then it is completely immersed in a liquid of known density, and the buoyancy of the battery in the liquid is measured. According to the buoyancy formula and the density formula, the actual density of the battery can be calculated; the porosity of the above-mentioned microcrystalline glassy sulfide battery at the end of the test cycle can be obtained by non-destructive X-ray computed tomography or scanning electron microscopy combined with image processing technology. Specifically, first ensure that the battery is in a stable state after the test and clean its surface, and then observe the slice sample of the microcrystalline glassy sulfide battery through a scanning electron microscope, and then use image processing software (such as Avi zo) to reconstruct or process the scanned or observed image, identify and calculate the pore area, and calculate the porosity of the battery according to the ratio of the pore area to the total volume or total area.
[0049] The theoretical density of the glass-ceramic sulfide battery is obtained, and the actual density of the glass-ceramic sulfide battery at the end of the test cycle is ratioed with the theoretical density of the glass-ceramic sulfide battery, and the processing result is marked as the density comparison value of the glass-ceramic sulfide battery at the end of the test cycle; the theoretical density of the glass-ceramic sulfide battery is obtained by multiplying the composition ratio of the sth key material of the glass-ceramic sulfide battery at the start of the manufacturing monitoring cycle with the corresponding density, and accumulating the results of the multiplication corresponding to different key materials, and the accumulated result is marked as the theoretical density of the glass-ceramic sulfide battery.
[0050] A conductivity change curve of the glass-ceramic sulfide battery during the test cycle is extracted from the conductivity detection parameters of the glass-ceramic sulfide battery during the test cycle, and a number of sample detection points are randomly arranged on the conductivity change curve to obtain the conductivity of each sample detection point and perform average processing, and the average processing result is marked as the average conductivity of the glass-ceramic sulfide battery during the test cycle; the conductivity change curve of the glass-ceramic sulfide battery during the test cycle is specifically obtained as follows: in the process of conducting a conductivity detection test on the glass-ceramic sulfide battery, the temperature of the glass-ceramic sulfide battery is continuously changed, and the conductivity of the glass-ceramic sulfide battery at different temperatures is tested using a conductivity tester, and the conductivity of the glass-ceramic sulfide battery at different temperatures is denoised and smoothly connected using matrix laboratory software, thereby obtaining the conductivity change curve of the glass-ceramic sulfide battery during the test cycle. In an exemplary embodiment, the conductivity change curve is as follows: Figure 3 As shown, it clearly shows that the conductivity of the microcrystalline glassy sulfide battery changes with temperature. The horizontal axis is temperature, the unit is Celsius, and the vertical axis is conductivity, the unit is Siemens / meter. The conductivity of each sample test point 1 is obtained and averaged to obtain the average conductivity.
[0051] It should be explained that the free electron concentration, density contrast value and porosity of the above-mentioned glassy sulfide microcrystalline battery at the end of the test cycle do not directly refer to the instantaneous value at the end of the test cycle, but specifically refer to the results obtained from the last test of electron concentration, density contrast value and porosity during the entire test cycle. Specifically, free electron concentration refers to the last test value of measuring the number of free electrons inside the glassy sulfide microcrystalline battery during the test cycle, which reflects the final state of the internal electron activity of the glassy sulfide microcrystalline battery after a series of tests. The density contrast value is the last test result obtained by comparing the actual density of the glassy sulfide microcrystalline battery with the theoretical density at the end of the test cycle. It is used to evaluate the final state of the density or porosity of the glassy sulfide microcrystalline battery material structure. Similarly, porosity is also the last test value of measuring the proportion of the internal pore volume of the glassy sulfide microcrystalline battery to the total volume during the test cycle, which reveals the final performance of the stability and integrity of the internal structure of the battery at the end of the test.
[0052] At the same time, the manufacturing process degradation factor of the glass-ceramic sulfide battery is integrated to obtain an evaluation method for the conductivity index of the glass-ceramic sulfide battery. In this embodiment, the conductivity index of the glass-ceramic sulfide battery is obtained by comprehensive analysis of the manufacturing process degradation factor of the glass-ceramic sulfide battery, the free electron concentration, density contrast value, porosity of the glass-ceramic sulfide battery at the end of the test cycle, and the average conductivity of the glass-ceramic sulfide battery during the test cycle. It is used to quantitatively evaluate the conductivity of the glass-ceramic sulfide battery. The specific evaluation method is as follows:
[0053]
[0054] MPD is the degradation factor of the manufacturing process of microcrystalline glassy sulfide batteries. If the degradation factor of the manufacturing process is large, it will have a more serious negative impact on the manufacturing stage of the microcrystalline glassy sulfide batteries, directly leading to a significant decrease in its conductive performance index.
[0055] FEC is the free electron concentration of the glassy sulfide microcrystalline battery at the end of the test cycle, which refers to the number of electrons that can move freely per unit volume in the glassy sulfide microcrystalline battery.
[0056] SGY is the density comparison value of the glassy sulfide microcrystalline battery at the end of the test cycle, which refers to the ratio of the actual density of the glassy sulfide microcrystalline battery to the theoretical density. It can be used to evaluate the density of the glassy sulfide microcrystalline battery material.
[0057] ROY is the porosity of the glassy sulfide microcrystalline battery at the end of the test period, which refers to the percentage of the pore volume in the glassy sulfide microcrystalline battery to the total volume.
[0058] DVC is the average conductivity of the glassy sulfide microcrystalline battery during the test cycle, which refers to the average value of the glassy sulfide microcrystalline battery's ability to conduct current during the test cycle.
[0059] K is the weight factor corresponding to the manufacturing process degradation factor preset in the detection database, which represents the proportion of the manufacturing process degradation factor to the conductivity performance index of the microcrystalline glassy sulfide battery. When used, the weight factor corresponding to the manufacturing process degradation factor can be directly obtained from the detection database, and the corresponding relationship can be a preset mapping relationship. For example, the manufacturing process degradation factor and the weight factor corresponding to the manufacturing process degradation factor preset in the detection database form a mapping set, and the real-time manufacturing process degradation factor is input into the mapping set to obtain the weight factor corresponding to the manufacturing process degradation factor. The mapping relationship can be one-to-one or many-to-one. In this example, its value range is [0, 1].
[0060] cn1 is the influence factor corresponding to the unit value of the free electron concentration preset in the detection database, which represents the influence degree of the unit value of the free electron concentration on the conductivity performance index of the microcrystalline glassy sulfide battery. When used, the influence factor corresponding to the unit value of the free electron concentration can be directly obtained from the detection database, and the corresponding relationship can be a pre-set mapping relationship. For example, the free electron concentration and the influence factor corresponding to the unit value of the free electron concentration preset in the detection database form a mapping set, and the real-time free electron concentration is input into the mapping set to obtain the influence factor corresponding to the unit value of the free electron concentration. The mapping relationship can be one-to-one or many-to-one. In this example, its value range is [0, 1].
[0061] cn2 is the influence factor corresponding to the unit value of the density contrast value preset in the detection database, which represents the influence degree of the unit value of the density contrast value on the conductivity performance index of the microcrystalline glassy sulfide battery. When used, the influence factor corresponding to the unit value of the density contrast value can be directly obtained from the detection database, and the corresponding relationship can be a pre-set mapping relationship. For example, the density contrast value and the influence factor corresponding to the unit value of the density contrast value preset in the detection database form a mapping set, and the real-time density contrast value is input into the mapping set to obtain the influence factor corresponding to the unit value of the density contrast value. The mapping relationship can be one-to-one or many-to-one. In this example, its value range is [0, 1].
[0062] cn3 is the influence factor corresponding to the porosity unit value preset in the detection database, which represents the influence degree of the porosity unit value on the conductivity performance index of the microcrystalline glassy sulfide battery. When used, the influence factor corresponding to the porosity unit value can be directly obtained from the detection database, and the corresponding relationship can be a pre-set mapping relationship. For example, the porosity and the influence factor corresponding to the porosity unit value preset in the detection database form a mapping set, and the real-time porosity is input into the mapping set to obtain the influence factor corresponding to the porosity unit value. The mapping relationship can be one-to-one or many-to-one. In this example, its value range is [0, 1].
[0063] cn4 is the influence factor corresponding to the average conductivity unit value preset in the detection database, which represents the influence degree of the average conductivity unit value on the conductivity performance index of the microcrystalline glassy sulfide battery. When used, the influence factor corresponding to the average conductivity unit value can be directly obtained from the detection database, and the corresponding relationship can be a pre-set mapping relationship. For example, the average conductivity and the influence factor corresponding to the average conductivity unit value preset in the detection database form a mapping set, and the real-time average conductivity is input into the mapping set to obtain the influence factor corresponding to the average conductivity unit value. The mapping relationship can be one-to-one or many-to-one. In this example, its value range is [0, 1].
[0064] Among them, CID is the conductivity index of the microcrystalline glass sulfide battery. A higher manufacturing process degradation factor indicates that the microcrystalline glass sulfide battery will introduce more defect impurities during the manufacturing process. These factors will reduce the conductivity of the microcrystalline glass sulfide battery. For example, the impurity atoms in the microcrystalline glass sulfide battery will interfere with the periodic potential field, form additional bound states, and reduce the concentration of free electrons. In the microcrystalline glass sulfide battery, the higher the free electron concentration, the more electrons can move freely under the action of the electric field, thus forming Current, therefore, the free electron concentration is positively correlated with the electrical conductivity. When the free electron concentration decreases, the electrical conductivity will also decrease accordingly, making the electrical conductivity at a lower level. When more micropores and cracks and other defects are introduced, it means that there are more voids and defects inside the microcrystalline glass sulfide battery, making the actual density of the microcrystalline glass sulfide battery lower than the theoretical density. At the same time, this high porosity defect will hinder the movement of electrons, thereby reducing the electrical conductivity of the microcrystalline glass sulfide battery, thereby jointly hindering the conductive performance of the microcrystalline glass sulfide battery.
[0065] In this exemplary embodiment, the conductivity performance index of the above-mentioned microcrystalline glass sulfide battery and its corresponding parameter change table are shown in Table 1:
[0066] Table 1 Changes in conductivity index and corresponding parameters of glass-ceramic sulfide batteries
[0067]
[0068]
[0069] In this example embodiment, the weight factor corresponding to the manufacturing process degradation factor is set to 0.21, and the influence factor corresponding to the unit value of the free electron concentration is set to 10. -22 , the value of the influence factor corresponding to the unit value of the density contrast value is set to 0.35, the value of the influence factor corresponding to the unit value of the porosity is set to 0.31, and the value of the influence factor corresponding to the unit value of the average conductivity is set to 0.0029. It can be seen from Table 1 that when the manufacturing process degradation factor is at a high level, that is, 210%, the free electron concentration, density contrast value and average conductivity are all at a low level, which are 10 21 The number of electrons / cubic meter, 83% and 800 Siemens / meter, however, the porosity is at a relatively high level of 12%, which comprehensively indicates that the conductivity of the microcrystalline glassy sulfide battery is at a low level, which is specifically reflected in the low conductivity performance index of 496%.
[0070] S3. Compare the expected conductivity level of the glass-ceramic sulfide battery with the actual conductivity level of the glass-ceramic sulfide battery. If the expected conductivity level of the glass-ceramic sulfide battery is less than or equal to the actual conductivity level of the glass-ceramic sulfide battery, continue manufacturing using the glass-ceramic sulfide battery manufacturing process parameters; otherwise, adjust the glass-ceramic sulfide battery manufacturing process parameters.
[0071] If the expected conductivity level of the glass-ceramic sulfide battery is less than or equal to the actual conductivity level of the glass-ceramic sulfide battery, that is, the glass-ceramic sulfide battery exhibits good conductivity during actual use, indicating that the glass-ceramic sulfide battery manufacturing process parameters can be continuously manufactured; conversely, if the expected conductivity level of the glass-ceramic sulfide battery is greater than the actual conductivity level of the glass-ceramic sulfide battery, that is, the glass-ceramic sulfide battery exhibits poor conductivity during actual use, the glass-ceramic sulfide battery manufacturing process parameters need to be further adjusted.
[0072] Specifically, the manufacturing process parameters of the glass-ceramic sulfide battery are adjusted, and the specific analysis process is: matching the adjustment requirement index of the glass-ceramic sulfide battery with the manufacturing adjustment set corresponding to each adjustment requirement index interval stored in the detection database, thereby obtaining the manufacturing adjustment set of the glass-ceramic sulfide battery, and adjusting the manufacturing process parameters of the glass-ceramic sulfide battery according to the manufacturing adjustment set of the glass-ceramic sulfide battery; in an example embodiment, the adjustment requirement index of a glass-ceramic sulfide battery is H, which belongs to the adjustment requirement index interval [H-43%, H stored in the detection database] +57%], the manufacturing adjustment set corresponding to the adjustment demand index range [H-43%, H+57%] includes: accurately adjusting the sintering temperature to 80% of the original temperature, that is, if the original temperature is X degrees Celsius, the adjusted temperature should be 0.8X degrees Celsius, and real-time monitoring of temperature fluctuations to ensure that the temperature stability is within ±1 degree Celsius, increasing the molding pressure, and the increase is controlled within 15% to 20% of the original pressure, adjusting the atmosphere of the sintering process, replacing the atmosphere with nitrogen with a purity of 99.9%, and in the early stage of sintering, the atmosphere flow rate can be controlled within the range of 1 to 2 cubic meters / hour to promote the material uniform heating and reaction. In the later stage of sintering, the atmosphere flow rate can be controlled within the range of 0.5-1 cubic meter / hour to promote the crystallization and densification of the material. The manufacturing adjustment set of the microcrystalline glassy sulfide battery includes accurately adjusting the sintering temperature to 80% of the original temperature, that is, if the original temperature is X degrees Celsius, the adjusted temperature should be 0.8X degrees Celsius, and real-time monitoring of temperature fluctuations to ensure that the temperature stability is within ±1 degree Celsius, increasing the molding pressure, and controlling the increase within 15% to 20% of the original pressure, adjusting the atmosphere of the sintering process, and replacing the atmosphere with nitrogen with a purity of 99.9%, In the initial stage of sintering, the atmosphere flow rate can be controlled within the range of 1 to 2 cubic meters per hour to promote uniform heating and reaction of the material. In the later stage of sintering, the atmosphere flow rate can be controlled within the range of 0.5 to 1 cubic meter per hour to promote crystallization and densification of the material. The intelligent control system receives the manufacturing adjustment set of the microcrystalline glass sulfide battery and performs automatic adjustments, so that the conductivity of the microcrystalline glass sulfide battery after manufacture can meet the actual use requirements. It should be noted that the manufacturing process adjustment parameters here are parameters for adjusting the manufacturing process of the next or next batch of microcrystalline glass sulfide batteries.
[0073] S4. Based on the expected conductivity level of the glass-ceramic sulfide battery, the actual conductivity level of the glass-ceramic sulfide battery and the conductivity performance index of the glass-ceramic sulfide battery, the adjustment requirement index of the glass-ceramic sulfide battery is determined, and the manufacturing process parameters of the glass-ceramic sulfide battery are adjusted accordingly.
[0074] In a specific embodiment, the present invention can accurately evaluate the current status and potential improvement space of the conductivity performance of the glass-ceramic sulfide battery by analyzing the expected conductivity level of the glass-ceramic sulfide battery, the actual conductivity level of the glass-ceramic sulfide battery and the conductivity performance index of the glass-ceramic sulfide battery, and then scientifically determine the degree of adjustment required for the glass-ceramic sulfide battery.
[0075] Specifically, the adjustment requirement index of the microcrystalline glassy sulfide battery is determined by the following specific determination process:
[0076] The average discharge power of the glass-ceramic sulfide battery during the test cycle is obtained, and the conductivity threshold of the glass-ceramic sulfide battery is extracted from the detection database; the conductivity threshold of the glass-ceramic sulfide battery refers to the minimum value of the reasonable range of the conductivity index of the glass-ceramic sulfide battery; the average discharge power of the glass-ceramic sulfide battery during the test cycle is obtained by setting the discharge current, discharge time and other parameters according to the characteristics and test requirements of the glass-ceramic sulfide battery, and setting the test cycle, including the test start time, end time and During the test interval, a discharge test is performed, the microcrystalline glassy sulfide battery is connected to the test equipment, and the discharge test is started. Multiple tests are performed under different discharge conditions, and the battery discharge voltage, discharge current, discharge time and other data are recorded. The instantaneous discharge power of each test is calculated based on the recorded discharge voltage and discharge current data. The calculation formula for the instantaneous discharge power is: P=V×I, where P is the discharge power, V is the discharge voltage, and I is the discharge current. The average value of each instantaneous discharge power is processed to obtain the average discharge power PR of the microcrystalline glassy sulfide battery during the test cycle.
[0077] The expected conductivity level of the glass-ceramic sulfide battery, the actual conductivity level of the glass-ceramic sulfide battery and the conductivity performance index of the glass-ceramic sulfide battery are comprehensively considered to obtain the adjustment requirement index of the glass-ceramic sulfide battery. In this embodiment, the adjustment requirement index of the glass-ceramic sulfide battery is obtained by comprehensive analysis of the conductivity performance index of the glass-ceramic sulfide battery, the conductivity performance threshold of the glass-ceramic sulfide battery, the actual conductivity level of the glass-ceramic sulfide battery, the expected conductivity level of the glass-ceramic sulfide battery and the average discharge power of the glass-ceramic sulfide battery in the test cycle, and is used to determine the value of the adjustment range of the glass-ceramic sulfide battery. The specific determination process is:
[0078]
[0079] CID ΔYis the conductivity threshold of the glassy sulfide microcrystalline battery, CID is the conductivity index of the glassy sulfide microcrystalline battery. If the difference between the conductivity threshold and the conductivity index is large, it indicates that the actual conductivity of the glassy sulfide microcrystalline battery is significantly different from the conductivity expected by the conductivity threshold, which further reflects that the glassy sulfide microcrystalline battery needs to be adjusted to a large extent.
[0080] ECG is the actual conductivity level of the microcrystalline glassy sulfide battery. ΔY is the expected conductivity level of the glassy sulfide microcrystalline battery. If the difference between the expected conductivity level and the actual conductivity level is large, it indicates that the actual conductivity of the glassy sulfide microcrystalline battery is far lower than the expected conductivity level, which further reflects that the glassy sulfide microcrystalline battery needs to be adjusted to a large extent.
[0081] PR is the average discharge power of the glassy sulfide microcrystalline battery during the test cycle, which refers to the average value of the discharge power of each test of the glassy sulfide microcrystalline battery during the test cycle.
[0082] ΔPR is the average discharge power reference value preset in the detection database, which represents the reference value of the average discharge power of the microcrystalline glassy sulfide battery during the test cycle.
[0083] A1 is the weight factor corresponding to the conductivity index deviation value preset in the detection database, which represents the proportion of the conductivity index deviation value to the adjustment demand index of the microcrystalline glassy sulfide battery. When used, the weight factor corresponding to the conductivity index deviation value can be directly obtained from the detection database, and the corresponding relationship can be a pre-set mapping relationship. For example, the difference between the conductivity threshold and the conductivity index and the weight factor corresponding to the conductivity index deviation value preset in the detection database form a mapping set, and the real-time conductivity threshold and the conductivity index difference are input into the mapping set to obtain the weight factor corresponding to the conductivity index deviation value. The mapping relationship can be one-to-one or many-to-one. In this example, its value range is [0, 1].
[0084] A2 is the influence factor corresponding to the actual conductivity level deviation unit value preset in the detection database, which represents the influence degree of the actual conductivity level deviation unit value on the adjustment demand index of the microcrystalline glassy sulfide battery. When used, the influence factor corresponding to the actual conductivity level deviation unit value can be directly obtained from the detection database, and the corresponding relationship can be a preset mapping relationship. For example, the difference between the expected conductivity level and the actual conductivity level and the influence factor corresponding to the actual conductivity level deviation unit value preset in the detection database form a mapping set, and the real-time expected conductivity level and the actual conductivity level difference are input into the mapping set to obtain the influence factor corresponding to the actual conductivity level deviation unit value. The mapping relationship can be one-to-one or many-to-one. In this example, its value range is [0, 1].
[0085] Among them, ADI is the adjustment demand index of the microcrystalline glassy sulfide battery. The larger the difference between the conductivity threshold and the conductivity index, the worse the conductivity of the microcrystalline glassy sulfide battery, and thus the lower the discharge power. This is because batteries with good conductivity can transmit current more efficiently, thereby releasing more electrical energy, while batteries with poor conductivity cannot release more electrical energy, resulting in a lower discharge power. At the same time, the smaller the conductivity index, the smaller the actual conductivity level obtained by matching, making the difference between the expected conductivity level and the actual conductivity level larger, indicating that the actual conductivity of the microcrystalline glassy sulfide battery is far lower than expected. Multiple unfavorable factors are intertwined, which makes the adjustment and optimization of microcrystalline glassy sulfide batteries in the manufacturing process particularly urgent.
[0086] In a specific embodiment, the present invention provides a method for detecting the conductivity of a battery, by collecting and analyzing the parameters of the manufacturing process of a glass-ceramic sulfide battery, thereby scientifically and accurately matching the expected conductivity level of the glass-ceramic sulfide battery, obtaining and evaluating the conductivity detection parameters of the glass-ceramic sulfide battery, thereby scientifically and accurately matching the actual conductivity level of the glass-ceramic sulfide battery, through comprehensive and in-depth data collection and analysis, the conductivity of the glass-ceramic sulfide battery can be quickly and accurately judged, reducing the errors and uncertainties caused by one-sided analysis, if the expected conductivity level of the glass-ceramic sulfide battery is less than or equal to the actual conductivity level of the glass-ceramic sulfide battery, then the glass-ceramic sulfide battery manufacturing process parameters are used to continue manufacturing, otherwise, timely feedback and guidance can be given to the adjustment of the glass-ceramic sulfide battery manufacturing process parameters, thereby ensuring that the conductivity of the glass-ceramic sulfide battery is at a high level.
[0087] Reference Figure 2As shown, the second aspect of the present invention provides a system using the method for detecting the conductivity of a battery as described, comprising: an expected conductivity analysis module, an actual conductivity evaluation module, a conductivity level comparison module and a battery manufacturing adjustment module.
[0088] The second aspect of the present invention provides a system for applying the method for detecting the conductivity of a battery as described above, and also includes a detection database, wherein the detection database is used to store the average sintering reference temperature, the sintering reference time, the average molding reference pressure, the reference component ratio of the sth key material, the expected conductivity level corresponding to each manufacturing process degradation factor interval, the weight factor corresponding to the manufacturing process degradation factor, the influence factor corresponding to the unit value of the free electron concentration, the influence factor corresponding to the unit value of the density contrast value, the influence factor corresponding to the unit value of the porosity, the influence factor corresponding to the unit value of the average conductivity, the actual conductivity level corresponding to each conductivity index interval, the manufacturing adjustment set corresponding to each adjustment requirement index interval, the conductivity threshold of the battery, the average discharge power reference value, the weight factor corresponding to the conductivity index deviation value, and the influence factor corresponding to the actual conductivity level deviation value unit value.
[0089] The expected conductivity analysis module is connected to the actual conductivity evaluation module, the actual conductivity evaluation module is connected to the conductivity level comparison module, the conductivity level comparison module is connected to the battery manufacturing adjustment module, and the expected conductivity analysis module, the actual conductivity evaluation module, the conductivity level comparison module and the battery manufacturing adjustment module are all connected to the detection database.
[0090] The expected conductivity analysis module is used to collect battery manufacturing process parameters, analyze the battery manufacturing process degradation factor, and match the expected conductivity level of the battery.
[0091] The actual conductivity evaluation module is used to obtain the conductivity detection parameters of the battery, and in combination with the degradation factor of the battery manufacturing process, evaluate the conductivity performance index of the battery and match the actual conductivity level of the battery.
[0092] The conductivity level comparison module is used to compare the expected conductivity level of the battery with the actual conductivity level of the battery. If the expected conductivity level of the battery is less than or equal to the actual conductivity level of the battery, the battery manufacturing process parameters are used to continue manufacturing. Otherwise, the battery manufacturing process parameters are adjusted.
[0093] The battery manufacturing adjustment module is used to determine the adjustment requirement index of the battery based on the expected conductivity level of the battery, the actual conductivity level of the battery and the conductivity performance index of the battery, thereby adjusting the battery manufacturing process parameters.
[0094] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the present invention, they should all fall within the protection scope of the present invention.
Claims
1. A method for detecting the conductivity of a battery, characterized in that: include: S1. Collect battery manufacturing process parameters, analyze the battery manufacturing process degradation factor, and match the expected conductivity level of the battery; S2. Obtain the conductivity detection parameters of the battery, and combine the degradation factor of the battery manufacturing process to evaluate the conductivity performance index of the battery and match the actual conductivity level of the battery; S3. Compare the expected conductivity level of the battery with the actual conductivity level of the battery. If the expected conductivity level of the battery is less than or equal to the actual conductivity level of the battery, continue manufacturing using the battery manufacturing process parameters. Otherwise, adjust the battery manufacturing process parameters. S4. Based on the expected conductivity level of the battery, the actual conductivity level of the battery, and the conductivity performance index of the battery, an adjustment requirement index of the battery is determined, thereby adjusting the battery manufacturing process parameters.
2. The method for detecting the conductivity of a battery according to claim 1, characterized in that: The manufacturing process degradation factor of the battery is analyzed, and the specific analysis process is as follows: Extracting the average sintering temperature of the battery during the manufacturing monitoring cycle, the sintering time of the battery during the manufacturing monitoring cycle, and the average molding pressure of the battery during the manufacturing monitoring cycle from the battery manufacturing process parameters; The composition ratio of each key material of the battery at the start time of the manufacturing monitoring cycle is extracted from the battery manufacturing process parameters, thereby comprehensively obtaining an analysis method for the degradation factor of the battery manufacturing process.
3. The method for detecting the conductivity of a battery according to claim 2, characterized in that: The manufacturing process degradation factor of the battery is analyzed by the following specific method: Among them, MPD is the degradation factor of the battery manufacturing process, ST is the average sintering temperature of the battery during the manufacturing monitoring cycle, SD is the sintering time of the battery during the manufacturing monitoring cycle, PD is the average molding pressure of the battery during the manufacturing monitoring cycle, CR is s is the composition ratio of the sth key material of the battery at the start time of the manufacturing monitoring cycle, ΔST is the average sintering reference temperature preset in the detection database, ΔSD is the sintering reference time preset in the detection database, ΔPD is the average molding reference pressure preset in the detection database, and ΔCR s To detect the reference composition ratio of the sth key material preset in the database, e is a natural constant, s is the number of each key material, s = {1, 2, 3, ..., p}, and p is the total number of key materials.
4. The method for detecting the conductivity of a battery according to claim 1, characterized in that: The expected conductivity level of the battery is matched, and the specific matching process is as follows: The manufacturing process degradation factor of the battery is matched with the expected conductivity level corresponding to each manufacturing process degradation factor interval stored in the detection database, thereby obtaining the expected conductivity level of the battery.
5. The method for detecting the conductivity of a battery according to claim 1, characterized in that: The obtaining of the conductivity detection parameters of the battery specifically refers to performing a conductivity detection test on the battery and obtaining the conductivity detection parameters of the battery during a test cycle.
6. The method for detecting the conductivity of a battery according to claim 1, characterized in that: The conductivity performance index of the battery is evaluated, and the specific evaluation process is as follows: Extracting the free electron concentration of the battery at the end of the test cycle, the actual density of the battery at the end of the test cycle, and the porosity of the battery at the end of the test cycle from the conductivity detection parameters of the battery during the test cycle; Obtain the theoretical density of the battery, and perform ratio processing on the actual density of the battery at the end time of the test cycle and the theoretical density of the battery, and mark the processing result as the density comparison value of the battery at the end time of the test cycle; Extracting a conductivity change curve of the battery during the test cycle from the conductivity detection parameters of the battery during the test cycle, randomly arranging a number of sample detection points on the conductivity change curve, obtaining the conductivity of each sample detection point and performing average processing, and marking the average processing result as the average conductivity of the battery during the test cycle; At the same time, the degradation factors of the battery manufacturing process are integrated to obtain an evaluation method for the battery's conductive performance index.
7. The method for detecting the conductivity of a battery according to claim 1, characterized in that: The actual conductivity level of the battery is matched, and the specific matching process is as follows: The conductivity performance index of the battery is matched with the actual conductivity level corresponding to each conductivity performance index interval stored in the detection database, thereby obtaining the actual conductivity level of the battery.
8. The method for detecting the conductivity of a battery according to claim 1, characterized in that: The battery manufacturing process parameters are adjusted, and the specific analysis process is as follows: The adjustment requirement index of the battery is matched with the manufacturing adjustment set corresponding to each adjustment requirement index interval stored in the detection database, thereby obtaining the manufacturing adjustment set of the battery, and the battery manufacturing process parameters are adjusted according to the manufacturing adjustment set of the battery.
9. The method for detecting the conductivity of a battery according to claim 1, characterized in that: The specific determination process of determining the adjustment requirement index of the battery is as follows: Obtain the average discharge power of the battery during the test cycle, and extract the battery's conductivity performance threshold from the detection database; A method for determining an adjustment requirement index of a battery is obtained by comprehensively considering the expected conductivity level of the battery, the actual conductivity level of the battery, and the conductivity performance index of the battery.
10. A system using the method for detecting the conductivity of a battery as claimed in any one of claims 1 to 9, characterized in that: include: The expected conductivity analysis module is used to collect battery manufacturing process parameters, analyze the battery manufacturing process degradation factors, and match the expected conductivity level of the battery; The actual conductivity evaluation module is used to obtain the conductivity detection parameters of the battery, and combined with the degradation factor of the battery manufacturing process, evaluate the conductivity performance index of the battery and match the actual conductivity level of the battery; A conductivity level comparison module is used to compare the expected conductivity level of the battery with the actual conductivity level of the battery. If the expected conductivity level of the battery is less than or equal to the actual conductivity level of the battery, the battery manufacturing process parameters are used to continue manufacturing. Otherwise, the battery manufacturing process parameters are adjusted. The battery manufacturing adjustment module is used to determine the adjustment requirement index of the battery based on the expected conductivity level of the battery, the actual conductivity level of the battery and the conductivity performance index of the battery, thereby adjusting the battery manufacturing process parameters.
Citation Information
Patent Citations
A device and method for testing the conductivity of graphene conductive paste.
CN116165458B
Battery detection device and battery detection method
CN116203421A
New energy battery health state monitoring method and system based on big data analysis
CN119224592A